![image](https://tex.z-dn.net/?f=+%2B%5Cleft+%5C%7B+%7B%7B+x%5E%7B2%7D+-2y%3D-1%7D+%5Catop+%7B4x%2B2y%3D-3%7D%7D+%5Cright.+%3D%3E+x%5E%7B2%7D+%2B4x%3D-4+%5C%5C++x%5E%7B2%7D+%2B4x%2B4%3D0+%5C%5C+%28x%2B2%29%5E2%3D0+%5C%5C+x%3D-2+%5C%5C+4%2A%28-2%29%2B2y%3D-3+%5C%5C+2y%3D5+%5C%5C+y%3D2%2C5+%5C%5C+%28-2%3B2%2C5%29)
x^{2} +4x=-4 \\ x^{2} +4x+4=0 \\ (x+2)^2=0 \\ x=-2 \\ 4*(-2)+2y=-3 \\ 2y=5 \\ y=2,5 \\ (-2;2,5)" alt=" +\left \{ {{ x^{2} -2y=-1} \atop {4x+2y=-3}} \right. => x^{2} +4x=-4 \\ x^{2} +4x+4=0 \\ (x+2)^2=0 \\ x=-2 \\ 4*(-2)+2y=-3 \\ 2y=5 \\ y=2,5 \\ (-2;2,5)" align="absmiddle" class="latex-formula">